Approaches to Recruiting School Principals in Russian University Cities as a Means of Educational Quality Enhancement - Bayburin R.F; Kasprzhak A.G; Filinov N.B (Moscow State University of Psychology and Education, 2018)
This paper discusses the outcome of the research that was conducted as part of the projects completed in the Centre for Leadership Development in Education, Institute of Education and Faculty of Business and Management, NRU HSE in 2017-2018.The research was carried out in two university cities of the Russian Federation - Moscow and Tomsk - and was based on Alan Rowe's methodology. The target of the research is the decision-making styles applied by state-funded school principals. The research aims to establish trends in the employment policy in the two cities and claims that it is characterized by the ratio of the number of principles with a peculiar decision-making style to the total number of principles in the sample. The paper contains questionnaire data, focus-groups data and transcripts of interviews with principles and members of their management teams. The outcome correlates with the major structural and employment reforms that have been made in Moscow within the last 7 years.